PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA MITSUTAMA TECHNOLOGY CIKARANG UTARA - Puspasari, Annisa; Maulia, Indah Rizki; Fikri, Adi Wibowo Noor (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of work motivation and work discipline on employee productivity at Mitsutama Technology Cikarang Utara. The research method used is an associative method with a quantitative approach. The type of data used is primary data obtained through interviews and questionnaires, while secondary data is obtained from information that already exists in the company that supports this research and comes from previous research such as books, journals, articles, and the like. The sampling technique used is non-probability sampling with the census sampling method, namely all members of the population totaling 40 employees are used as research samples. The data analysis technique used in this study is Partial Least Square (PLS) which is processed with Smart PLS software. The results of the study indicate that work motivation and work discipline have a positive and significant effect on employee productivity. Thus it can be concluded that work motivation and work discipline have a positive and significant effect on employee productivity, both directly and indirectly.